The New Solitary Confinement? A Conceptual Framework for Guiding and Assessing Research and Policy on “Restrictive Housing” - Mears, Daniel P. (Criminal justice and behavior, 2019)
As part of the rise of “get tough” punishment in recent decades, prison systems increasingly have relied on solitary confinement and what many contemporary accounts have termed “restrictive housing.” The latter includes an emphasis on some form of isolation and restrictions on privileges. Use of solitary-like confinement has engendered considerable debate because of differing views about whether it is moral or effective and whether it harms inmates. Despite this debate and the ubiquity of solitary-like confinement, there is much that remains unknown about its uses or effects. A central reason stems from inconsistent operationalizations of such housing in research and policy. This situation creates problems in generalizing the results of studies to diverse settings and populations. The goals of this article are to highlight these points and to advance scholarship and policy debates by presenting a conceptual framework for guiding and assessing research on restrictive housing.